Answer:
B = (2, -5)
Step-by-step explanation:
The problem requirements mean ...
B - A = (2/3)(C - A)
B = A + (2/3)C - A
B = (1/3)A + (2/3)C = (A +2C)/3
B = ((-6, 1) +2(6, -8))/3 = (-6+12, 1-16)/3 = (6, -15)/3
B = (2, -5)
Answer:
all of ABOVW
Step-by-step explanation:
Answer:
20
Step-by-step explanation:
Cause im smart and you should trust me. duh
The standard form of a line:

We have the equation of a line in the slope-point form:
use distributive property
add 3 to both sides
multiply both sides by 2
subtract x from both sides
change the signs
